Båndoptagelser som kilde til Ømålsordbogen - Gudiksen, Asgerd; Hovmark, Henrik (Nordiske Studier i Leksikografi, 2007)
Use of tape recordings as empirical basis at Ømålsordbogen. The aim of Ømålsordbogen (The Dictionary of the Insular Dialects) is to embrace the whole vocabulary of the dialects, dialecticisms as well as words in common with standard Danish. The dictionary is based on a collection of approximately 3 million slips, excerpted from various sources. The major portion of the material, however, has been collected by the staff itself. Despite a thorough work trying to cover all of the vocabulary, a number of words and expressions are poorly attested in the collection of slips. This goes especially for function words and frequent words with no striking difference in use or meaning between standard and dialect – words of this kind have often been left unnoticed both when recording data and when excerpting. A corpus of transcribed tape recordings has therefore turned out to be a useful supplement. And the corpus has not only permitted a more adequate description of function words etc., it has also provided the dictionary with more authentic quotations.